Suitability of aonla (Emblica officinalis) cultivars for development of osmo air dried slices - SINGH, JAGMOHAN; KUMAR, RAKESH; BAKSHI, PARSHANT; BANDRAL, JULIE D; SOOD, MONIKA; TRILOKIA, MEENAKSHI (The Indian Journal of Agricultural Sciences, 2015)
The present study was undertaken to find out most suitable cultivar of aonla (Emblica officinalis Gaertn.) for development of value added products, i.e. osmo-air dried slices from four aonla cultivars, viz. Banarasi, Chakaiya, NA7 and Desi. The osmo air dried slices were prepared using sugar syrup of 700 Brix, citric acid for 24 hrs and dried at 600C. The slices were packed in polythene pouches and stored at ambient conditions to observe the effect of storage on quality and shelf life. The prepared samples were analysed for various quality parameters. An increasing trend was observed in the acidity, where as total sugars, reducing sugars, water activity and ascorbic acid content showed a decreasing trend in all the four cultivars. The highest acidity (4.68 %) was found in Desi cultivar, whereas the highest total sugars and reducing sugar (43.42 %, 33.02 %, respectively) were recorded in Chakaiya after 135 days of storage. The acceptability of the product was evaluated in terms of colour, flavour, taste and overall acceptability. The highest mean score for colour (7.12), texture (7.59), flavour (7.68) and overall acceptability (7.43) was found in Chakaiya followed by Banarasi cultivar. Thus, both Chakaiya and Banarasi were found to be suitable cultivars for making of osmo air dried slices.